Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Toko Baju Kaos Nyenyes Palembang - Hilwa Anggraini; Muhammad Deni; Imam Suroso; Aras Tulip; Tutik Pebrianti (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
Nyenyes t-shirt shop Palembang is one of many souvenir shops in Palembang which is in generally the customers are from every level of society starting from Palembang residents and tourists visiting Palembang. Nyenyes t-shirt shop itself has many funny, unique designs and makes visitors who visit the shop laugh because the design images cover the typical Empek-empek city such as the names of food, tourist attractions, and words that are often spoken by the people of Palembang themselves make Nyenyes t-shirt shop known by the people from and Outside Palembang. The research problem in this study is how much theeffect of service quality on customer satisfaction. The purpose is to determine the effect of Service Quality Effect on Customer Satisfaction. The samples are 50 visitors who came to Nyenyes t-shirt shop. The data collection techniques used in this study are interviews and questionnaires. Based on the research results, there is effect of service quality on customer satisfaction at Nyenyes T-shirt shop in Palembang, the sig t is 0.000 <0.05. The simple linear regression equation is Y = 15,974 + 0,321X + e. The coefficient of determination Rsquare is 0.720. These results indicate that service quality has an effect on customer satisfaction at Nyenyes t-shirt shop Palembang by 72%, while the remaining 28% is explained by other variables outside of this research.